2021
DOI: 10.1016/j.radcr.2021.09.022
|View full text |Cite
|
Sign up to set email alerts
|

Myxopapillary ependymoma with interval postoperative CSF seeding: A report of an unusual case

Abstract: Myxopapillary ependymoma (MPE) is a unique slow-growing benign (WHO grade 1) subtype of spinal cord ependymoma arising predominantly in the filum terminale. Despite its benign nature, it occasionally disseminates through the cerebrospinal fluid and metastasizes to distant sites. Here, we report an extremely rare case of MPE with interval CSF seeding and metachronous metastasis in a 47 –year-old female presented as a gradually increasing low back pain for three months with bilateral radiculopathy down to the kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…It is important to note that there are situations where complete surgical removal is not possible due to various factors such as tumor location, size, or involvement of critical structures. Additionally, during surgical resection, it is crucial to be mindful of the risk of seeding, which refers to the potential spread of tumor cells caused by the surgical procedure itself [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that there are situations where complete surgical removal is not possible due to various factors such as tumor location, size, or involvement of critical structures. Additionally, during surgical resection, it is crucial to be mindful of the risk of seeding, which refers to the potential spread of tumor cells caused by the surgical procedure itself [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Abdallah et al 21 reported GTR of one drop metastasis, whereas Lee et al 22 reported GTR of a maximum of two masses at the time of surgery. Lastly, Abdu et al 23 described a case in which one mass was removed by GTR. Thus, to the best of our knowledge, our illustrative case with GTR of five lesions is the greatest number of lesions removed by GTR in the setting of disseminated MPE at the time of recurrence.…”
Section: Discussionmentioning
confidence: 99%